Proteomics Evidence for the Activity of the Putative Antibacterial Plant Alkaloid (-)-Roemerine: Mainstreaming Omics-Guided Drug Discovery - SARIYAR AKBULUT, BERNA (MARY ANN LIEBERT, INC, 2015)
Discovery of new antibacterials with novel mechanisms is important to counteract the ingenious resistance mechanisms of bacteria. In this connection, omics-guided drug discovery offers a rigorous method in the quest of new antibacterials. (-)-Roemerine is a plant alkaloid that has been reported to possess putative antibacterial activity against Escherichia coli, Bacillus subtilis, and Salmonella typhimurium. The aim of the present study was to characterize the activity of (-)-roemerine in Escherichia coli TB1 using proteomics tools. With (-)-roemerine treatment, we found limited permeability through the outer membrane and repression of transport proteins involved in carbohydrate metabolism, resulting in poor carbon source availability. The shortfall of intracellular carbon sources in turn led to impaired cell growth. The reduction in the abundance of proteins related to translational machinery, amino acid biosynthesis, and metabolism was accompanied by a nutrient-limited state. The latter finding could suggest a metabolic shutdown in E. coli cells. High osmolarity was clearly not one of the reasons of bacterial death by (-)-roemerine. These observations collectively attest to the promise of plant omics and profiling of putative drug candidates using proteomics tools. Omics-guided drug discovery deserves greater attention in mainstream pharmacology so as to better understand the plants' medicinal potentials.
Keywords: OUTER-MEMBRANE PROTEINS; TYROSINE-PHOSPHATASE INHIBITORS; ESCHERICHIA-COLI; APORPHINE ALKALOIDS; ISOQUINOLINE ALKALOIDS; NELUMBO-NUCIFERA; RESISTANCE; OMPX; EXPRESSION; OSMOREGULATION